LncRNA AGAP2-AS1 Facilitates Tumorigenesis and Ferroptosis Resistance through SLC7A11 by IGF2BP2 Pathway in Melanoma. (6th June 2022) - An, Lifeng; Huang, Jingwen; Ge, Shihui; Zhang, Xin; Wang, Jing
Abstract : Long noncoding RNAs (lncRNAs) stand as indispensable regulators of initiation and development in melanoma (melanoma). However, the action molecular mechanisms linked to melanoma remain unclear. In the current study, the findings revealed that AGAP2-AS1 was considerably greater in melanoma than in healthy tissues and that the level of AGAP2-AS1 in cancer tissue was significantly linked to the cancerous TNM stage of patients. Individuals with high AGAP2-AS1 had a considerably shorter survival duration than patients with low AGAP2-AS1, regardless of progression-free survival or overall survival. Functionally, downregulating the expression of AGAP2-AS1 can inhibit the growth of melanocytes. Compared with the control group, AGAP2-AS1 knockdown increased Erastin-mediated iron death in melanoma cells. However, iron death inhibitor FERSINT-1 restored this effect, while Erastin induced melanoma cell death. Besides, intracellular iron and Fe 2+ levels increased after AGAP2-AS1 knockdown in melanoma cells treated with Erastin compared with the si-NC group. In addition, AGAP2-AS1 silencing resulted in a significant decrease in glutathione (GSH) content in Erastin-treated melanoma cells. The mechanistic results suggest AGAP2-AS1 increases SLC7A11 mRNA stability through the IGF2BP2 pathway. In this investigation, we discovered new activities for AGAP2-AS1 and firstly discovered its mechanistic basis in ferroptosis and melanoma formation that might help in the search for potential therapy options in melanoma.